2002
DOI: 10.1074/jbc.m204734200
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for DNA Methyltransferase DNMT3B in Cancer Cell Survival

Abstract: Abnormal methylation and associated silencing of tumor suppressor genes is a common feature of many types of cancers. The observation of persistent methylation in human cancer cells lacking the maintenance methyltransferase DNMT1 suggests the involvement of other DNA methyltransferases in gene silencing in cancer. To test this hypothesis, we have evaluated methylation and gene expression in cancer cells specifically depleted of DNMT3A or DNMT3B, de novo methyltransferases that are expressed in adult tissues. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 32 publications
6
106
1
Order By: Relevance
“…As a result of its de novo methyltransferase activity, DNMT3b is an attractive candidate for the other DNMT that contributes to tumor suppressor gene silencing. In support of this notion, antisense suppression of DNMT3b in tumor cell lines restored tumor suppressor gene expression (Beaulieu et al, 2002) as did deletion of DNMT3b in DNMT1-deficient HCT116 (Rhee et al, 2002). Nonetheless, the precise contribution of DNMT3b to tumor progression and transformation is unknown.…”
Section: Introductionmentioning
confidence: 64%
“…As a result of its de novo methyltransferase activity, DNMT3b is an attractive candidate for the other DNMT that contributes to tumor suppressor gene silencing. In support of this notion, antisense suppression of DNMT3b in tumor cell lines restored tumor suppressor gene expression (Beaulieu et al, 2002) as did deletion of DNMT3b in DNMT1-deficient HCT116 (Rhee et al, 2002). Nonetheless, the precise contribution of DNMT3b to tumor progression and transformation is unknown.…”
Section: Introductionmentioning
confidence: 64%
“…Unlike DNMT1, DNMT3b has been suggested to be site-selective in the regulation of aberrant gene silencing. DNMT3b expression has also been found to be essential for cancer cell survival by inhibiting apoptosis of tumour cells but not normal cells (Beaulieu et al, 2002). The results of in vitro studies by Geiman et al (2004) further indicate that DNMT3b contributes to gene silencing by recruiting chromatin remodeling histone deacetylase.…”
Section: Discussionmentioning
confidence: 95%
“…An early in vitro study using the colon carcinoma cell line HCT116 reported that DNMT3B interacts with DNMT1 to silence gene expression in human cancer cells (Rhee et al, 2002). Recent studies have suggested that DNMT3B is required for tumor development (Beaulieu et al, 2002). Furthermore, DNMT3B1 efficiently methylates the same set of genes in both tumor and non-tumor tissues, demonstrating that the de novo methylation activity of methyltransferase 3B is essential to gene silencing.…”
Section: Discussionmentioning
confidence: 99%